Analisis Kesiapan Guru dalam Penerapan Kurikulum Merdeka pada Pembelajaran Seni Rupa di SMP Negeri 21 Padang - Ridwan Hanafi; Yusron Wikarya (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2025)
The goal of this study is to analyze the readiness of teachers in the application of the Independent Curriculum in art learning and obstacles in art learning at SMP Negeri 21 Padang. Qualitative research using a descriptive approach is the methodology employed. The informant in this study is the Deputy Head of Curriculum and a cultural arts teacher in the field of fine arts class VIII in preparing for the implementation of the independent curriculum. This study collects data through documentation, interviews, and observation. Based on data processing, it was found that the readiness of teachers in the implementation of the independent curriculum in art learning at SMP Negeri 21 Padang has been carried out well. cultural arts teachers only refer to the Teaching Module and the teaching method activities still use the old method, but in the learning system it has been applied based on the independent curriculum structure. There are various difficulties that stem from the quality of cultural arts teachers who teach, inadequate facilities and infrastructure for art exhibition activities.